2008
DOI: 10.1017/s1355617708081368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal alcohol exposure on hippocampal volume, verbal learning, and verbal and spatial recall in late childhood

Abstract: Children with prenatal alcohol exposure (PAE) show deficits in verbal learning and spatial memory, as well as abnormal hippocampal development. The relationship between their memory and neuroanatomic impairments, however, has not been directly explored. Given that the hippocampus is integral for the synthesis and retrieval of learned information and is particularly vulnerable to the teratogenic effects of alcohol, we assessed whether reduced learning and recall abilities in children with fetal alcohol spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
164
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 60 publications
10
164
1
Order By: Relevance
“…Impairment in memory (e.g., problems remembering information learned recently; repeatedly making the same mistakes; difficulty remembering long verbal instructions) 5. Impairment in visual spatial reasoning (e.g., disorganized or poorly planned drawings or constructions; problems differentiating left from right; problems aligning numbers in columns) hippocampal volume have been linked to functional memory impairments in human neuroimaging studies [41,42] and animal models [39,43]. Active working memory, which involves the capacity to store and process meaningful units at a given moment in time, has been found to be deficient in individuals with PAE, particularly for tasks involving multiple-step instructions [31].…”
Section: Memory Deficitsmentioning
confidence: 99%
“…Impairment in memory (e.g., problems remembering information learned recently; repeatedly making the same mistakes; difficulty remembering long verbal instructions) 5. Impairment in visual spatial reasoning (e.g., disorganized or poorly planned drawings or constructions; problems differentiating left from right; problems aligning numbers in columns) hippocampal volume have been linked to functional memory impairments in human neuroimaging studies [41,42] and animal models [39,43]. Active working memory, which involves the capacity to store and process meaningful units at a given moment in time, has been found to be deficient in individuals with PAE, particularly for tasks involving multiple-step instructions [31].…”
Section: Memory Deficitsmentioning
confidence: 99%
“…1 Children with such disorders can have a range of developmental problems such as language delay, behavior problems, and cognitive deficits in IQ, 2 learning, memory, [3][4][5][6][7] attention, 6,8,9 and motor functioning, 6 all of which can have a negative impact on educational achievement. 10 Research has demonstrated an association between prenatal alcohol exposure and poor performance in preacademic skills that predict numerical problem solving and reading proficiency.…”
mentioning
confidence: 99%
“…10 Research has demonstrated an association between prenatal alcohol exposure and poor performance in preacademic skills that predict numerical problem solving and reading proficiency. 11,12 Learning and memory deficits are reported to be the most common cognitive effects of prenatal alcohol exposure, 5 with reports of deficits occurring in verbal, 3,5,7 nonverbal, 4 and visuospatial learning. 5 The quantity and timing of prenatal alcohol exposure associated with deficits in child learning ability varies across studies and the type of outcome examined.…”
mentioning
confidence: 99%
“…Among pregnant women, the rate of any illicit drug use is 5.4% and has not changed significantly since 2010-2011 [12]. Use remains higher in younger women (14.6%, ages 18-25) compared to older women (3.2%, ages [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. A high proportion of women are using marijuana illegally and fail to disclose their use to their providers.…”
Section: Current Prevalence Estimates Of Prenatal Drug Exposurementioning
confidence: 99%
“…Prenatal alcohol is associated with overall reductions in global [38,39] and regional brain volume including the hippocampus, basal ganglia, cingulate cortex, and corpus callosum [37,[40][41][42][43]. Several studies indicate that reductions in brain volume linked to prenatal alcohol exposure were associated with deficits in cognitive function and facial dsymorphology.…”
Section: Maternal and Environmental Variablesmentioning
confidence: 99%